Pronephros in Sheep (Ovis aries) - Prasad, D. V. V. N. Durga; Nagamalleswari , Y.; Raju, N. K. B. (International Journal of Livestock Research, 2018)
The present research work carried out in 11 embryos and foetuses of local Nellore sheep from 20 days (0.7 cm CRL) to 31 days (2 cm CRL) of gestation. The tissue samples were fixed in 10% NBF and Bouin’s fluid and processed for routine histological studies. The pronephros was located on either side of the dorsal aorta which was surrounded by undifferentiated mesenchymal cells in 20 day (0.7 cm CRL) old embryo. It showed one giant glomerulus of 225±1.3µm in size and many tubules were present in the pronephros, some tubules were fully formed and some other was incomplete and open type. At 27 days of gestation (1.7 cm CRL) the degenerative changes were noticed in glomerular network due to which vacuolation was noticed between the tuft of glomerulus. The complete degeneration of pronephros with proliferating mesenchymal tissue replaced with degenerated structures by 31 days (2 cm CRL) of gestation.